A long-term survivor of ITGA3-related infantile lethal nephrotic syndrome with epidermolysis bullosa - Kumar, Sailesh I. S.; Nimmakanty Ramadas, Ashok; Vel Shantharam, Raja; Sivanandam, Sivsankar; Nallathambi, Naveenkumar (International Journal of Contemporary Pediatrics, 2026)
Infantile lethal nephrotic syndrome with epidermolysis bullosa (ILNEB) syndrome is an autosomal recessive genodermatosis caused by biallelic variants in ITGA3 (integrin subunit alpha 3; 17q21.33), disrupting α3β1 integrin-mediated adhesion in epithelial basement membranes. Canonical features-progressive interstitial lung disease (ILD), congenital/infantile nephrotic syndrome (CNS/INS), and junctional epidermolysis bullosa (JEB)-manifest neonatally with >95% mortality by age 2 years across 22 reported cases. A 9-year-old female from consanguineous pedigree presented with chronic respiratory insufficiency, stunting, mechanobullous dermatosis, and nephrotic-range proteinuria (4.95 g/1.73 m²/day). Multimodal diagnostics, including histopathology and trio-exome sequencing, confirmed homozygous in ITGA3 exon 8, diagnostic of ILNEB. Despite multisystem involvement, multidisciplinary palliation yielded sustained remission. This index case of protracted survival delineates ITGA3-related phenotypic heterogeneity, advocates genomic ascertainment in paediatric ILD-CNS-JEB triads, and posits supportive therapies as longevity modifiers.